'Arbitrary and cruel punishments': Trends in Royal Navy courts martial, 1860–1869. (August 2021) - Johnston, Andrew
Despite minor amendments to the Royal Navy's Articles of War throughout the eighteenth century, and a major reworking in 1749, both capital and corporal punishments were frequently employed as punishment for minor offences in a system that made England's 'Bloody Code' look positively humane. The 1860 Naval Discipline Act provided the first substantive overhaul of the original Articles of War, but historians have generally lamented this act as providing little comprehensive change to the governance of the navy. Using statistical data collected from thousands of courts martial records, this article takes a broad look at trends in naval courts martial, studying how these courts interacted with the legislative changes of the 1860s. Viewing how charges and sentences altered on the global scale, it becomes clear that the 'arbitrary and cruel punishments' of the previous century had at last given way to a centralized, formal expression of discipline.